Developing Principles for the Regulation of Microinsurance: Philippine Case Study - Gilberto M. Llanto; Maria Piedad S. Geron; Joselito Almario (Philippine Institute for Development Studies (PIDS), 2008)
Illness or injury, death of a family member, man-made calamities and natural disasters have a devastating effect on those poor households' cash flow, liquidity, and earning capacities and thus, on household welfare. Demand for microinsurance products is growing in view of continuing risks to household welfare and the seeming inability of the government to address this issue. This study seeks to provide a better understanding of the microinsurance market in the Philippines and to draw certain principles for microinsurance regulation from a review of the Philippine experience with microinsurance. The study describes how policies, legal, regulatory, and supervisory framework governing insurance have shaped the development of the market and vice versa. The Philippine experience on the provision of microinsurance services and the interaction between the insurance providers and the regulator may help inform the development of certain principles for microinsurance regulation.
Keywords: 330; moral hazard; microinsurance; catastrophic events; market conduct regulation; product regulation